Carious status and socio-behavioral risk factors among 12 year-old children in South-Central region in Romania - Ruxandra Sfeatcu; Mariana Cărămidă; Ruxandra Sava-Rosianu; Marius Lupșa Matichescu; Atena Galuscan; Mihaela Adina Dumitrache (BMC, 2023)
Abstract Background Regular screenings at children population level are necessary in order to assess communities' need for education, prevention, as well as early detection and intervention programs The study aims to assess dental caries experience and oral health-related behaviors among Romania children from the South and Central region. Methods The cross-sectional study conducted in 2019-2020 is part of the national survey "Romanian Oral Health Survey", under the endorsement of the World Health Organization (WHO). The stratified, randomized and representative sample included 98 children of 12 years of age. The assessment included a clinical examination, using International Caries Detection and Assessment System (ICDAS) and the Oral Health Questionnaire for Children recommended by the World Health Organization. Results Results revealed that the frequency of caries-free children among 12 year-olds was 36.7% and the mean DMFT was 2.89. Regarding the oral health-related habits, 38.8% of children brushed twice daily; the consumption of sugary foods multiple times per day has been frequently met and 11.2% at the age of 12 never visited the dental office. Conclusions The findings revealed that caries prevalence was high and behaviors negatively influence oral health. The presented data are of utmost importance for Romanian policy makers to promote oral health education among children, to support consistent preventive oral health campaigns and to stimulate dental attendance, irrespective of children' living areas or gender.